2018
DOI: 10.1016/j.livsci.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions associated with performance in racing line of Quarter Horses

Abstract: Quarter Horses breed for rancing are able to run short distances faster than any other breed. Although in Brazil the effective number of animals in the racing line is relatively smaller compared to the other lines, its economic importance is substantial. Despite economic and scientific interest in this athletic trait, few efforts have been made to better understand the genetic and physiological mechanisms underlying this trait. The objective of this study was to perform genome-wide association studies (GWAS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(77 reference statements)
0
4
0
1
Order By: Relevance
“…In the studies of Pereira et al (2018Pereira et al ( , 2019, who used the single-step GBLUP method to estimate the effect of thousands of SNPs and genomic regions on SImax in the same racing Quarter Horses as used in the present study, one of the regions/windows on ECA15 found to be associated with the trait of interest harbors the SLC3A1 gene whose variant was also related to racing performance of Quarter Horses in the present study. In addition to this coincidence, these authors also found other regions that were relatively close (distance of 1.6 Mb) to the CCN6 (ECA10).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the studies of Pereira et al (2018Pereira et al ( , 2019, who used the single-step GBLUP method to estimate the effect of thousands of SNPs and genomic regions on SImax in the same racing Quarter Horses as used in the present study, one of the regions/windows on ECA15 found to be associated with the trait of interest harbors the SLC3A1 gene whose variant was also related to racing performance of Quarter Horses in the present study. In addition to this coincidence, these authors also found other regions that were relatively close (distance of 1.6 Mb) to the CCN6 (ECA10).…”
Section: Discussionmentioning
confidence: 95%
“…Association studies between DNA polymorphisms and racing performance in horses have been performed mainly on Thoroughbred horses, including punctual association analysis (candidate gene strategy) (Gu et al, 2010;Hill et al, 2010) and GWASs (Shin et al, 2015;Farries et al, 2019). However, some results obtained for Quarter Horses in both punctual genome analysis (Pereira et al, 2016a(Pereira et al, , 2016b and GWASs (Pereira et al, 2018) showed that the markers appropriate for the English breed are generally not suitable for the identification of superior racing animals of the North American breed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other genes are related to these two breeds, such as PPP4R2, PDZRN3 and SHQ1. It may be explained due to Thoroughbred being one of The horse breeds used in The formation of The racing line of Quarter Horses, and thus it is observed that The results of genetic studies involving these two breeds may be similar [19].…”
Section: Gene-tf Networkmentioning
confidence: 99%
“…The 10-SNP windows that explained more than 1% of the genetic variance were considered promising regions and used to identify potential candidate genes by using the National Center for Biotechnology Information (NCBI) database and Ensembl Genome Browser (http: / / www .ensembl .org/ index .html) through the biomaRt R package (http: / / www .bioconductor .org; Ensembl release 90). The threshold of 1% was chosen to identify the most important windows and to use the level used in other studies (e.g., Gonzalez-Pena et al, 2016;Zhu et al, 2017;Marques et al, 2018;Pereira et al, 2018). The Manhattan plots were created using qqman package (Turner, 2014).…”
Section: Gwasmentioning
confidence: 99%